2014
DOI: 10.2166/wp.2014.095
|View full text |Cite
|
Sign up to set email alerts
|

Inverse infrastructures: self-organization in the water services

Abstract: In urban communities, infrastructures that support living are indispensable. There is increased interest in alternative ways of providing such support systems, including semi-autonomous infrastructures resulting from the selforganization of local actors. In this study, we analyze the emergence and management of such infrastructures in light of the theory of complex adaptive systems, within which they are called 'inverse infrastructures'. Empirical evidence is drawn from the case of water cooperatives in the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…It is worth noticing that all articles consider multiple actors in the governance process: the public actors (public departments and agencies) at the regional and national level remain important, as public officials at these levels are responsible to keep an overview of the water systems and for harmonizing standards, for example, drinking water quality. However, we also find that citizens and consumers (local communities) become important players in the context of user-driven modular and decentralized infrastructures (Bakker & Cook, 2011; Heino & Anttiroiko, 2015; Simon & Lehn, 2012).…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…It is worth noticing that all articles consider multiple actors in the governance process: the public actors (public departments and agencies) at the regional and national level remain important, as public officials at these levels are responsible to keep an overview of the water systems and for harmonizing standards, for example, drinking water quality. However, we also find that citizens and consumers (local communities) become important players in the context of user-driven modular and decentralized infrastructures (Bakker & Cook, 2011; Heino & Anttiroiko, 2015; Simon & Lehn, 2012).…”
Section: Resultsmentioning
confidence: 82%
“…In terms of market-based instruments, the articles focus on subsidies and loans, as they can function as a catalyst for an innovation’s distribution (Gaulke, 2006; Heino & Anttiroiko, 2015; Schramm et al, 2017). Other market-based instruments addressed in the literature are procurement auctions and further economic incentives, which have the potential to encourage the adoption of new systems, such as the installation of parcel-scale rain gardens and rain barrels within a small suburban watershed, or support developments in the sector (Thurston et al, 2010; Simon et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Inverse infrastructures rely on the local community and users for their creativity and ability to invest and operate instead of a professionally driven comprehensive design that is based on predictability. Research has shown that one prerequisite for the development of microinfrastructures is that the infrastructure policy of cities supports and enables self-organization of local communities to produce water services; thus, the implementation of hybridization is also a question of encountering two different ways of governing (Heino & Anttiroiko, 2015). Furthermore, it has been observed that with self-organizing microinfrastructures people perceive their efforts to be more meaningful and to reflect societal responsibility (Egyedi, 2012; Egyedi & Mehos, 2012).…”
Section: Hybridization Of Water Servicesmentioning
confidence: 99%